2014
DOI: 10.1038/ncomms6121
|View full text |Cite
|
Sign up to set email alerts
|

A scaling law for random walks on networks

Abstract: The dynamics of many natural and artificial systems are well described as random walks on a network: the stochastic behaviour of molecules, traffic patterns on the internet, fluctuations in stock prices and so on. The vast literature on random walks provides many tools for computing properties such as steady-state probabilities or expected hitting times. Previously, however, there has been no general theory describing the distribution of possible paths followed by a random walk. Here, we show that for any rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
4
23
0
1
Order By: Relevance
“…SSR processes can be related to diffusion processes on directed networks. For a specific example we demonstrated that the visiting times of nodes follow a Zipf's law, and could further reproduce very general recent findings of path-visit distributions in random walks on networks [27]. Here we presented results for a completed directed graph, however we conjecture that SSR processes on networks and the associated Zipf's law of node-visiting distributions are tightly related and are valid for much more general directed networks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…SSR processes can be related to diffusion processes on directed networks. For a specific example we demonstrated that the visiting times of nodes follow a Zipf's law, and could further reproduce very general recent findings of path-visit distributions in random walks on networks [27]. Here we presented results for a completed directed graph, however we conjecture that SSR processes on networks and the associated Zipf's law of node-visiting distributions are tightly related and are valid for much more general directed networks.…”
Section: Discussionsupporting
confidence: 86%
“…5 (b) (black dashed line), which shows the observed path rank distribution for the 2 N −1 = 16 paths. For cyclic processes, where at least one node participates in at least two distinct cycles, [27] predicts power-laws, which we clearly confirm for the cyclic Φ mix process with p exit = 0.3 (red line). Note that in our example node 1 alone is involved in 5 distinct cycles.…”
Section: Examplessupporting
confidence: 71%
See 1 more Smart Citation
“…We call diffusion processes on DAG structures targeted diffusion, since, in this type network, diffusion is targeted towards a set of target or sink nodes, see figure 1(e). The targeted diffusion results we present here are in line with recent findings reported in [29].…”
supporting
confidence: 93%
“…Our current statistical inference methods in modelling cancer Waddington landscapes (network state-space) mainly comprise of graph theory, classical information theory, Bayesian networks, cluster analysis and machine learning algorithms (9)(10)(11). Due to the stochastic nature of molecules, the transitions between the attractors of the landscape are defined by random walks on a network (i.e., Brownian motion) (12). That is, the fluctuations around the epigenetic barriers of the landscapes are governed by diffusion equations (13)(14)(15).…”
mentioning
confidence: 99%